Analysis of the Open Unemployment Determinants in Regencies and Cities in Central Java - Kusumaputra, Fadhil Reyhan; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2026)
Abstract: This study examines determinants of the open unemployment rate across 35 regencies/cities in Central Java during 2018–2025. Explanatory variables include average years of schooling, population size, regency/city minimum wage, GRDP growth, and a Covid-19 dummy. Panel data regression using Fixed Effect with Driscoll-Kraay standard errors shows that average years of schooling and GRDP growth negatively and significantly affect unemployment, while population size and minimum wage are not significant. The Covid-19 dummy has a positive significant effect, indicating the pandemic increased unemployment by approximately 1.02 percentage points. All variables are simultaneously significant with a Within R² of 0.4534. Findings highlight the importance of improving education, promoting employment-absorbing economic growth, and strengthening labor market resilience against external shocks.